NARCOTICS - A MISFORTUNE UNDER A BEAUTIFUL SHADOW: A MIRAGE THAT DECEIVES SOCIETY (American Journal of Research in Humanities and Social Sciences, 2026)
The article presents analyses of issues related to countering narcotic agents - one of the global problems of the modern world. The causes and consequences of their distribution are also considered, and scientific proposals and recommendations on measures to combat them are given.